Analisis Peningkatan Kontrol Warehouse Trucking Melalui Strategi Business Process Mapping Pada PT. Berkah Multi Cargo - Prasetiyo Agung Wijaya; Abdurrahman Faris Indriya Himawan (Universitas Muhammadiyah Gresik, 2022)
The process of trucking at the warehouse at PT Berkah Multi Cargo (BMC) Logistics there is a problem where the trucking data input process in the warehouse is still done manually. This makes the process of distributing information in each division take a long time, therefore there is a need for improvement. The purpose of this study is to analyze to improve control of the trucking process at the warehouse. The type of research used in this study is a type of qualitative research with a descriptive approach. While the data collection techniques used in this study were observation and face to face interviews. Informants / resource persons or subjects in the study were determined by purposive sampling. The results of this study can be used as a reference by companies, especially logistics companies to improve control of the warehouse trucking process by creating systems such as the Business Process Modeling Notation (BPMN) describing a business process diagram based on flow chart techniques. This research is limited to PT Berkah Multi Cargo (BMC) Logistics, to make a system it takes people who are experts in the IT field so that the system can be implemented.